Supportive Educative Nursing Program Effectively Increasing Self Care for Heart Failure Patients - Ida Ayu Agung Laksmi; Putu Wira Kusuma Putra; I Kadek Sudika (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Heart failure patients generally experience activity intolerance resulting in functional limitations and decreased of self care abilities. One of the systems identified Orem in patients with self-care fulfillment barriers is the supportive educational system, which is an effort to provide assistance to patients who need educational support in the hope that patients will be able to need independent care. The purpose of this study was to determine the effect of supportive educational programs on self care for heart failure patients. This research method was a quasy-experimental research with a pre-post-test control group design approach. A sample of 28 respondents were divided into treatment groups that received a supportive educational program and a control group that was given education according to discharge planning procedures at Mangusada Regional Hospital. The questionnaire used was Self Care Heart Failure Index (SCHFI). Data were analyzed using Independent T-test. The result of this study showed that there were significant differences between self care in the intervention and control group with a p-value (0.017), where p < (0.05) which means that statistically providing supportive educational programs was more effective compared to ordinary education. Providing supportive educational programs can be used as nursing interventions to improve independent care of patients with heart failure.